Creating an imaginary context: teacher's use of embodied enactments in addressing learner initiatives in a beginner-level adult ESOL classroom. Issue 3 (2nd September 2018) - Tai, Kevin W. H.; Brandt, Adam
ABSTRACT: Previous research has illustrated that learner initiatives have the potential to generate learning opportunities in second language (L2) classrooms. Despite a small body of recent research indicating that teachers' responses to learner initiatives play a significant role in facilitating learning opportunities in teacher–student interactions, more work is needed to understand the resources teachers draw upon in their responses. This study contributes to this by examining how a teacher employs what we term 'embodied enactments' as a pedagogical tool to contingently respond to learner initiatives. Using Conversation Analysis, we examine a single case taken from a corpus of video data collected in a beginner-level adult English for Speakers of Other Languages classroom in the United States. The findings reveal that the teacher contingently and multimodally enacts imaginary contexts which help students to understand how the target vocabulary and phrases can be used in everyday life. In doing this, the teacher and students are bridging the gap between classroom discourse and language use outside of the classroom, providing interactional space for promoting L2 learning.